A Critical Review Of Accountability From The Islamic Perspective: Phenomena, Position, And Alignment Of Methodology - Nasyi'ah, Eny Zuhrotin; Triyuwono, Iwan; Djamhuri, Ali; Ghofar, Abdul (The International Journal of Accounting and Business Society, 2022)
Purpose—This paper aims to critically review currently developing conventional public accountability and reconstruct it based on an Islamic perspective. It will also provide a strategic position of Islamic values in the methodology used in accountability research. Design/methodology/approach — This paper employed a secondary research approach emphasizing the wholeness in viewing accountability and using Islamic values as the primary comparative research material. Findings —  Our findings placed Islam uniquely positioned with a strategic value in public accountability and methodology alignment. Practical implications —  Accountability within the perspective of Islam will provide intrinsic values and benefits for those dealing with public accountability reporting. We expect this paper to imply massively applying the new public accountability concept. Originality/value—This paper presents the internalization of the Ihsan value within Islam as a guide and supervisor of people dealing with accountability. It also proposes a hybrid accountability concept from the perspectives of accounting and Islam.